Formation of Humic-Like Substances during the Technological Process of Lignohumate® Synthesis as a Function of Time - Olga Yakimenko; Andrey Stepanov; Svetlana Patsaeva; Daria Khundzhua; Olesya Osipova; Oleg Gladkov (Separations, 2021)
The composition, structure, and biological activity of humic-like substances (HLS) synthesized in the process of lignosulfonate conversion for the production of the humic product Lignohumate® (LH) were examined. It is shown that during the hydrolytic-oxidative process, the transformation of raw material and accumulation of HLS occur. Data on the chemical (elemental content, functional groups, FTIR) and spectral (absorbance and fluorescence) parameters and biological activity (in phytotest) combined with PCA show that the LH samples can be divided into three groups, depending on the duration of synthesis: initial raw material (0-time sample); “young” HLS (15–30 min), and “mature” HLS in 45–120 min of treatment. During the first 30 min, reactions similar to the ones that occur during lignin humification in nature take place: depolymerization, oxidative carboxylation, and further polycondensation with the formation and accumulation of HLS. After 45–60 min, the share of HLS reaches a maximum, and its composition stabilizes. Biological activity reaches a maximum after 45–60 min of treatment, and at that stage, the further synthesis process can be stopped. Further processing (up to 2 h and more) does not provide any added value to the humic product.